museum, Majapahit MUSEUM MAJAPAHIT DI TAHUN 2018-2019 SEBAGAI SARANA PENDIDIKAN DAN REKREASI SERTA TEMPAT BERSEJARAH - Ahmad Muhib Zuhairy (LP4MK STKIP PGRI Lubuklinggau, 2020)
On April 24, 1924 R.A.A Kromodjojo Adinegoro, one of the Regents of Mojokerto, collaborated with Ir. Henry Maclaine Pont, an architect of Balanda, founded Oudheidkundige Vereeniging Majapahit (OVM), an association aimed at examining Majapahit's heritage. However, the OVM has undergone many name changes and has also moved a lot from the past to the present. Until now it is known as the PIM (Majapahit Information Center) which is protected by the BPCB JATIM (Cultural Heritage Conservation Center). Until now, the Majapahit Information Center (PIM) or often called the Trowulan Museum is currently located on Jl. Pendopo Agung, Dusun Unggahan, Trowulan Village, Kec. Trowulan, Kab. Mojokerto, East Java Province. This building is located on a land area of 54,935 mm. The museum consists of 3 main buildings namely buildings a, b, and c and small buildings.1) Building A, is a residential building located in the western part of the city. and is the main building of the museum until now. 2) Building B, a building built in 1926 is a semi-open building with wooden walls and a joglo shaped roof. The location of the building is to the east of building A, slightly protruding from the sea. 3) Building C, this building was founded in 1927 and was completed around 1928. The building is located to the east of building B. The shape of the building is quite interesting because the overall shape is similar to starfruit.